Genetic diversity and relationships of selected Polygonum species using RAPD analysis - Maha, Maharajan; Rajendran, Arumugam; Das, Jayashankar (Research in Plant Biology, 2014)
The genetic diversity of the selected Polygonum species namely P. chinense L., P. molle D. Don, P. glabrum Willd., P. barbatum L., P. fagopyrum Moench. P.hydropiper, P.nepalances, was analyzed using RAPD markers.